FORTÆLLINGER OM FEDTSUGERE OG VOLD: Mod en forståelse af skabelsen af voldens betydning - Rønsbo, Henrik (Tidsskriftet Antropologi, 2002)
During the last ten years it has been argued by anthropologists that violence is constadictory to processes through which meaning is created and sustained, i.e. everyday life. This argument derives from the empirical branches of psychology and psychiatry, which, since the early seventies, have formalized various concepts regarding post-traumatic stress, the best known of which is the concept of PTSD. Taking a point of departure in an alternative understanding of violence as the production of enigmatic signifiers, rather than the destruction of signification and meaning, the author demonstrates how enigmatic signifiers through processes of entextualization are circulated. Hence